2014
DOI: 10.3390/atmos5020230
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Speciation at a Coastal Site in the Northern Gulf of Mexico: Results from the Grand Bay Intensive Studies in Summer 2010 and Spring 2011

Abstract: Abstract:During two intensive studies in summer 2010 and spring 2011, measurements of mercury species including gaseous elemental mercury (GEM), gaseous oxidized mercury (GOM), and particulate-bound mercury (PBM), trace chemical species including O 3 , SO 2 , CO, NO, NO Y , and black carbon, and meteorological parameters were made at an Atmospheric Mercury Network (AMNet) site at the Grand Bay National Estuarine Research Reserve (NERR) in Moss Point, Mississippi. Surface measurements indicate that the mean mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 41 publications
4
18
0
Order By: Relevance
“…The Canadian sites are located in Point Petre and Egbert, Ontario (Blanchard et al, 2002); CAMNet stations (Temme et al, 2007), Toronto (Cheng et al, 2009), northwestern Ontario (Cheng et al, 2012); Kejimkujik National Park (Cheng et al, 2013a); Flin Flon, Manitoba (Eckley et al, 2013); Fort McMurray, Alberta (Parsons et al, 2013); and Windsor, Ontario (Xu et al, 2014). The US sites included south Florida (Graney et al, 2004); Detroit, Michigan (Lynam and Keeler, 2006;Liu et al, 2007); Mount Bachelor, Oregon (Swartzendruber et al, 2006); Athens, Ohio (Gao, 2007); Rochester, New York (Huang et al, 2010); and Grand Bay, Mississippi (Ren et al, 2014). Most of the studies identified a factor/component that was representative of combustion sources (e.g., coal combustion, vehicular, industrial, biomass burning, and waste incineration emissions) regardless of whether the studies were conducted in urban, rural, or coastal locations.…”
Section: Source Apportionmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The Canadian sites are located in Point Petre and Egbert, Ontario (Blanchard et al, 2002); CAMNet stations (Temme et al, 2007), Toronto (Cheng et al, 2009), northwestern Ontario (Cheng et al, 2012); Kejimkujik National Park (Cheng et al, 2013a); Flin Flon, Manitoba (Eckley et al, 2013); Fort McMurray, Alberta (Parsons et al, 2013); and Windsor, Ontario (Xu et al, 2014). The US sites included south Florida (Graney et al, 2004); Detroit, Michigan (Lynam and Keeler, 2006;Liu et al, 2007); Mount Bachelor, Oregon (Swartzendruber et al, 2006); Athens, Ohio (Gao, 2007); Rochester, New York (Huang et al, 2010); and Grand Bay, Mississippi (Ren et al, 2014). Most of the studies identified a factor/component that was representative of combustion sources (e.g., coal combustion, vehicular, industrial, biomass burning, and waste incineration emissions) regardless of whether the studies were conducted in urban, rural, or coastal locations.…”
Section: Source Apportionmentmentioning
confidence: 99%
“…This component included strong positive component loadings on GOM, O 3 , temperature and wind speed, and negative loadings on relative humidity (Lynam and Keeler, 2006). Other studies also extracted a component representative of GEM oxidation with similar pollutant or meteorological parameter loadings; however, the component did not explain the most variance with percentages ranging from 11 to 27 % (Li et al, 2008;Huang et al, 2010;Cheng et al, 2012Cheng et al, , 2013aRen et al, 2014;Xu et al, 2014). GEM oxidation was also inferred from a PCA component containing GOM, BrO and O 3 (Ren et al, 2014).…”
Section: Source Apportionmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The system was operated according to National Atmospheric Deposition Program Atmospheric's (NADP) Mercury Network (AMNet) protocol [31], except a shorter sample/analysis period (2.5 min) was used. The system was located next to a hangar where the aircraft parked.…”
Section: Ground-based Measurementsmentioning
confidence: 99%
“…The Great Lakes region has been one focus of study [2][3][4], while mercury pollution in the Gulf of Mexico region has also drawn increasing attention in recent years [5]. The observed atmospheric wet deposition flux of mercury in the Gulf of Mexico region is higher than that in any other region in the United States [6][7][8]. This is at least partly due to the relatively high rainfall rates in the region, as well as the higher prevalence of tall convective thunderstorms, resulting in the increased scavenging of free tropospheric mercury [9].…”
Section: Introductionmentioning
confidence: 99%